Implementasi Metode Talaqqi dalam Menghafal Hadis di SD Islam Tahfizh Al-Qur'an At-Tauhid Pangkalpinang - Putra, Julius Adi; Waluyo, Muhammad Edy; Jauhari, Muhammad Insan (LENTERNAL: Learning and Teaching Journal, 2024)
The talaqqi method is the right method to implement in memorizing hadith, because this method is easy to use and effective in implementation. This can be seen from students who can achieve the targets set in memorizing hadiths even more. Because in its application students face directly with educators when memorizing hadiths, so students can see directly how educators pronounce hadiths. And by implementing the talaqqi method, educators can supervise and monitor the development of students' memorization directly. This research was motivated by curiosity about the implementation of the Talaqqi Method in Memorizing Hadith at the Tahfizh al-Qur'an at-Tauhid Pangkalpinang Islamic Elementary School. This research aims to examine. First, the implementation of the talaqqi method in memorizing hadith at the Tahfizh al-Qur'an at-Tauhid Pangkalpinang Islamic Elementary School. Second, the advantages and disadvantages of the talaqqi method in memorizing hadith at the Tahfizh al-Qur'an at-Tauhid Pangkalpinang Islamic Elementary School. This type of research is qualitative descriptive research which presents research results reports and describes the data obtained regarding the implementation of the talaqqi method in memorizing hadith at the Tahfizh al-Qur'an at-Tauhid Pangkalpinang Islamic Elementary School. The research subjects consisted of 1 school principal, 5 educators and 5 students. The research data sources obtained are primary data sources and secondary data sources. This research data collection technique uses non-participant observation, interviews and documentation. Meanwhile, the data analysis method uses data reduction, data presentation and verification. Based on the research results, it shows that the implementation of the talaqqi method is carried out in three stages. First, preparation, starting with greetings, dhikr, checking attendance, neatness and order, and preparing tools. The second implementation is starting with murojaah together and handing over the memorization to the educators in turn. Third, evaluation, evaluation is carried out on the memorization that has been submitted. And in its implementation, this talaqqi method has advantages and disadvantages